2018
DOI: 10.1200/cci.16.00079
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Approach for Variant Reporting

Abstract: Purpose Next-generation sequencing technologies are actively applied in clinical oncology. Bioinformatics pipeline analysis is an integral part of this process; however, humans cannot yet realize the full potential of the highly complex pipeline output. As a result, the decision to include a variant in the final report during routine clinical sign-out remains challenging. Methods We used an artificial intelligence approach to capture the collective clinical sign-out experience of six board-certified molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Fusions for MYB‐NFIB or MYBL1‐NFIB (40%) and NOTCH1 mutations (25%) were the most common alterations. Across all cancer types tested in our institution (n = 2,701 cases were genotyped between 2013 and 2018) , we have only seen MYB and MYBL1 fusions in adenoid cystic carcinomas (specificity: 100%) . We modeled that even if a non‐ACC would harbor one MYB/MYBL1 fusion, it would take ∼14 cases of non‐ACC for the specificity to drop below 99.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusions for MYB‐NFIB or MYBL1‐NFIB (40%) and NOTCH1 mutations (25%) were the most common alterations. Across all cancer types tested in our institution (n = 2,701 cases were genotyped between 2013 and 2018) , we have only seen MYB and MYBL1 fusions in adenoid cystic carcinomas (specificity: 100%) . We modeled that even if a non‐ACC would harbor one MYB/MYBL1 fusion, it would take ∼14 cases of non‐ACC for the specificity to drop below 99.5%.…”
Section: Resultsmentioning
confidence: 99%
“…genotyped between 2013 and 2018) [27,37], we have only seen MYB and MYBL1 fusions in adenoid cystic carcinomas (specificity: 100%) [38]. We modeled that even if a non-ACC would harbor one MYB/MYBL1 fusion, it would take 14 cases of non-ACC for the specificity to drop below 99.5%.…”
Section: Comutational Landscape Of Acc In Clinical Practicementioning
confidence: 99%
“…Massachusetts General Hospital (MGH) did the experiment and got very promising results. They selected ~ 500 features, built multiple ML models on ~ 20,000 clinical sign-out variants reported by board-certified molecular pathologists and then compared the prediction results to find the best model (Zomnir et al 2018 ). The logistic regression model demonstrated the best performance with only 1% false negativity and 2% false positivity, which is comparable to human decisions.…”
Section: Precision Medicine and Aimentioning
confidence: 99%
“…For instance, in one study, Watson for Genomics identified genomic alterations with potential clinical impact that were not recognized by the traditional molecular tumor boards in 323 (32%) of patients using an analysis that took only a few minutes (Patel et al 2018 ). At MGH, the clinical implementation of an AI-based decision support tool for variant reporting allows molecular pathologists to quickly make decisions and empowers them to explore the underlying reasoning behind them (Zomnir et al 2018 ). As we move to an age of AI, medical education must move beyond the foundational biomedical and clinical sciences to knowledge of information platforms and intelligence tools in healthcare and the skills to effectively use them (Wartman and Combs 2018 ).…”
Section: Challenges To Ai Adoption In Healthcarementioning
confidence: 99%
“…The use of artificial intelligence in clinical oncology, genome interpretation, and especially in variant reporting has gained momentum. 49,50 Data available from manually classified variants can be used to train deep neural networks. 49 The advantage of this approach is that the algorithm is able to autonomously extract relevant features for classification and identify important combinations not only for genetic information but for all types of biomarker.…”
Section: Tomorrowmentioning
confidence: 99%